HXE 201- Report Writing and Editing in English - November 2005 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (2005)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic Session 2005/2006 November 2005 HXE 201- Report Writing and Editing in English Duration: 3 hours